2021
DOI: 10.1186/s13098-021-00738-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the internet combined with exercise-based individualized nursing intervention in patients with gestational diabetes mellitus

Abstract: Background Gestational diabetes mellitus (GDM) is the most frequent medical complication of pregnancy. This condition is manifested by glucose intolerance resulting in hyperglycemia of variable severity during pregnancy. One of the most important clinical tools for efficiently regulating maternal blood glucose is strictly monitoring blood glucose levels. However, due to a lack of appropriate intervention tools, managing the occurrence of GDM is still unfeasible. This study aimed to determine cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Chen Y et al [ 25 ] applied the combination of IoT and exercise-based individualized nursing intervention in the treatment of 139 patients with GDM. The results showed that the IoT combined with individualized exercise-based nursing intervention could effectively improve patients' blood glucose, insulin resistance, and psychological state, thus significantly improving their pregnancy outcome and mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Chen Y et al [ 25 ] applied the combination of IoT and exercise-based individualized nursing intervention in the treatment of 139 patients with GDM. The results showed that the IoT combined with individualized exercise-based nursing intervention could effectively improve patients' blood glucose, insulin resistance, and psychological state, thus significantly improving their pregnancy outcome and mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, further studies are needed to explore which lifestyle treatment options could best improve perinatal outcomes in obese women and whether there are some effective interventions to help reduce maternal weight before pregnancy, such as bariatric surgery. Thirdly, a series of effective strategies such as diet, physical exercise, weight management, and blood glucose self-monitoring should be followed by pregnant women during their pregnancy (31)(32)(33)(34). For instance, Chen et al (33) recently showed that internet combined with individualized exercise-based nursing intervention in GDM women can significantly reduce the high blood glucose levels and improve their pregnancy outcomes in relation to routine nursing intervention only.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, a series of effective strategies such as diet, physical exercise, weight management, and blood glucose self-monitoring should be followed by pregnant women during their pregnancy (31)(32)(33)(34). For instance, Chen et al (33) recently showed that internet combined with individualized exercise-based nursing intervention in GDM women can significantly reduce the high blood glucose levels and improve their pregnancy outcomes in relation to routine nursing intervention only. A randomized controlled trial by Bruno et al (34) displayed that the adherence to a personalized, hypocaloric, low-glycemic, low-saturated fat diet started at the early pregnancy stage can prevent the occurrence of GDM in women with ppBMI ≧ ̸ 25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, blood glucose control for pregnant women is essential to protect the health and safety of mothers and fetuses. When pregnant women were diagnosed with GDM, they are frequently recommended to do more exercise and eat regularly [ 8 ]. Drug intervention may only be considered when the target blood glucose level can still not be reached after exercise intervention.…”
Section: Introductionmentioning
confidence: 99%